Correlation between the presence of tonsilloliths and the bone defects by periodontitis on imaging analysis: a pilot study - Masafumi Oda; Shinji Yoshii; Nao Wakasugi-Sato; Shinobu Matsumoto-Takeda; Ikuko Nishida; Shun Nishimura; Susumu Nishina; Manabu Habu; Daigo Yoshiga; Masaaki Sasaguri; Yasuhiro Morimoto (BMC, 2024)
Abstract Background Very recently, a significant relationship between tonsilloliths and dental plaque-related pathologies was reported using digital panoramic radiographs. Their dynamics over time suggest that tonsilloliths may be in a permanently active phase that functions to remove foreign matter. The aim of the study was to evaluate the relationship between the occurrence of tonsilloliths and the extent of periodontitis. Methods A total of 608 patients who underwent both CT and panoramic radiographs were included in the study. Both of two imaging were retrospectively and independently assessed with respect to the presence of tonsilloliths detected on CT and panoramic radiographs, and bone defects caused by periodontitis detected on panoramic radiographs. The type of retrospective study is case-control. Then, the differences between age groups were evaluated with respect to the degree of bone resorption and its correlation with the presence of tonsilloliths. The relationships between categorical variables were assessed using Pearson's correlation coefficient or Spearman's correlation coefficient. Results There was a significant relationship between tonsilloliths on CT and the extent of the bone defect on panoramic radiographs (Spearman's correlation coefficient, r = 0.648, p = 0.043). In addition, there was a significant difference in the extent of the bone defect caused by periodontitis between subjects with and without tonsilloliths in the 60 to 69-year-old group (Mann-Whitney U test, p = 0.025), 70 to 79-year-old group (Mann-Whitney U test, p = 0.002), and 80 to 89-year-old group (Mann-Whitney U test, p = 0.022), but not in other age groups (Mann-Whitney U test: under 9-year-old group, p = 1.000; 10 to 19-year-old group, p = 1.000; 20 to 29-year-old group, p = 0.854; 30 to 39-year-old group, p = 0.191, 40 to 49-year-old group, p = 0.749; 50 to 59-year-old group, p = 0.627; ≥90-year-old group, p = 1.000). Conclusions The presence of tonsilloliths was related to the extent of periodontitis because the structures were responding dynamically.